Arterioarterial Prosthetic Loop as an Alternative Approach for Hemodialysis Access. Issue 41 (October 2015) - Lei, Wenhui; Ji, Jiansong; Wang, Jian; Jin, Lie; Zou, Hai
Abstract : Abstract: In the present study, we performed an arterioarterial prosthetic loop (AAPL) between the femoral artery and deep femoral artery as a new access in patients who did not have adequate vascular conditions for creating an arteriovenous fistula or graft. Between April 2005 and June 2014, 18 patients received AAPL as a vascular access. During the procedure, a polytetrafluoroethylene graft was anastomosed to the femoral artery and deep femoral artery and looped on the thigh. We assessed the reliability and safety of AAPLs by analyzing complication, primary and secondary patency rates, and postoperative blood flow. Eighteen patients (median age, 66 years; range, 43–96 years) underwent AAPL access placement under the general or local anesthesia. All patients were followed up for 3 to 38 months (mean, 24 months). Primary and secondary patency rates at 6 months were 94.5% and 88.8%, respectively, and at 3 years were 61% and 72%, respectively. After operation, one patient had infection, and another one had fat necrosis at the surgical incision site. To maintain the AAPL function, 5 surgical procedures in 4 grafts, including revision, thrombectomy, excision, and repair for bleeding were performed. More than 5000 hemodialyses were performed efficiently in our center. Our study shows that AAPL loop is an unusual but effective and safe procedure that may be a good alternative for the patients who do not allow the conventional hemodialysis access.